2018
DOI: 10.1158/1541-7786.mcr-17-0715
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Progression Is Mediated by Thymosin-β4 through a TGFβ/MRTF Signaling Axis

Abstract: Although enhanced thymosin β4 (TMSB4X/Tβ4) expression is associated with tumor progression and metastasis, its tumor-promoting functions remain largely unknown. Here, it is demonstrated that TGFβ facilitates Tβ4 expression and leads to the activation of myocardin-related transcription factors (MRTF), which are coactivators of serum response factor (SRF) and regulate the expression of genes critical for the epithelial-mesenchymal transition (EMT) and tumor metastasis. In murine mammary gland cells (NMuMG), Tβ4 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…This indicates the ability of the vaccine to activate the immune system and limit glioma progression. We found that thymosin, a hormone that stimulates T-cell maturation, 23 demonstrated weak antitumor effect in the rat glioma models. A slight increase in peripheral and tumor-infiltrating CD4+ T cells, but not in CD8+ T and NK cells, was observed in the thymosin treatment group.…”
Section: Discussionmentioning
confidence: 91%
“…This indicates the ability of the vaccine to activate the immune system and limit glioma progression. We found that thymosin, a hormone that stimulates T-cell maturation, 23 demonstrated weak antitumor effect in the rat glioma models. A slight increase in peripheral and tumor-infiltrating CD4+ T cells, but not in CD8+ T and NK cells, was observed in the thymosin treatment group.…”
Section: Discussionmentioning
confidence: 91%
“…The function of the five proteins is related to the progress of tumor cell biology. Out of these five proteins, DCP1A regulates Atg12 and is linked to autophagy and proteasome degradation pathways [40], TMSB4X regulates TGFβ1 and participates in the progression of cancer [41], MGST3 increases in the LT97 adenoma cells and participates in cancer development [42], AKR1C2 is a key enzyme in the process of progesterone metabolism and is closely related to gynecological tumor development [43], and ERLIN1 is influences the survival time of pancreatic cancer patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Thymosin-ß4 (Tß4; TMSB4X) and THBS1 are considered as tumor promoters with a poor prognosis in different types of cancers (25)(26)(27)(28). Interestingly, TMSB4X has a function in the TGF-ß/Tß4/MRTF signaling pathway, leading to EMT induction and metastasis (36). SRSF6 behaves as an oncogene protein and is associated with proliferation, transformation, and tumorigenicity of immortal cancer cells (37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%